Calcium signalling by nicotinic acid adenine dinucleotide phosphate (NAADP). - Yamasaki, M; Churchill, G; Galione, A (2005)
Nicotinic acid adenine dinucleotide phosphate (NAADP) is a recently described Ca2+ mobilizing messenger, and probably the most potent. We briefly review its unique properties as a Ca2+ mobilizing agent. We present arguments for its action in targeting acidic calcium stores rather than the endoplasmic reticulum. Finally, we discuss possible biosynthetic pathways for NAADP in cells and candidates for its target Ca2+ release channel, which has eluded identification so far.